2023
DOI: 10.3390/ijms24076263
|View full text |Cite
|
Sign up to set email alerts
|

iE-DAP Induced Inflammatory Response and Tight Junction Disruption in Bovine Mammary Epithelial Cells via NOD1-Dependent NF-κB and MLCK Signaling Pathway

Abstract: γ-D-glutamyl-meso-diaminopimelic acid (iE-DAP), a bacterial cell wall component, can trigger an inflammatory response. A mammary inflammatory response causes tight junction (TJ) dysfunction. This study aimed to explore the effects and involved mechanisms of iE-DAP-induced inflammatory response on the TJ integrity in bovine mammary epithelial cells (BMECs). The results showed that iE-DAP-induced inflammatory response and TJ disruption was associated with increased expression levels of inflammatory cytokines and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Previous studies have shown that NF-κB modulates the LPS-induced TJ injury by targeting the expression level of the TJ effector protein MLCK . Increased MLCK can phosphorylate downstream proteins, destroy the interaction between TJ proteins and the cytoskeleton, induce the redistribution of ZO-1 and occludin, and damage TJ integrity. , While MLCK inhibitor administration decreases MLCK expression and increases TJ protein expression, thus ameliorates barrier dysfunction. , The study has also shown that butyrate treatment leads to the inhibition of MLCK, which further restores TJ protein distribution and TJ barrier function in Caco-2 . Consistent with previous studies, we also found that butyrate significantly reduced the protein expression of MLCK in BMECs compared with the DAP group.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…Previous studies have shown that NF-κB modulates the LPS-induced TJ injury by targeting the expression level of the TJ effector protein MLCK . Increased MLCK can phosphorylate downstream proteins, destroy the interaction between TJ proteins and the cytoskeleton, induce the redistribution of ZO-1 and occludin, and damage TJ integrity. , While MLCK inhibitor administration decreases MLCK expression and increases TJ protein expression, thus ameliorates barrier dysfunction. , The study has also shown that butyrate treatment leads to the inhibition of MLCK, which further restores TJ protein distribution and TJ barrier function in Caco-2 . Consistent with previous studies, we also found that butyrate significantly reduced the protein expression of MLCK in BMECs compared with the DAP group.…”
Section: Discussionmentioning
confidence: 87%
“…First of all, BMECs were exposed to a gradient concentration of SB (0.1, 0.5, 1, 2, and 4 mM) for 24 h to assay the effect of SB on cell viability. Based on our previous study and the result of cell viability, 22 cells were further exposed to 1000 ng/mL iE-DAP with various concentrations of SB (0.1, 0.5, 1, and 2 mM) for 12 h to detect the regulatory effects of SB on the iE-DAP-triggered inflammatory response and TJ injury. Next, cells were treated with 1000 ng/mL iE-DAP with or without 2 mM SB for 12 h to further assay the nuclear transfer of NF-κB p65, the cellular distribution of ZO-1, and the integrity of the TJ barrier.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 3 more Smart Citations